Energetic materials and munitions : life cycle management, environmental impact, and demilitarization - Cumming, Adam Stewart; Johnson, Mark S. (Toxicologist) (Wiley-VCH, 2019)
This book gives an overview of the environmental impact of the production, use, and cleanup of energetic materials and munitions. It provides scientists, engineers, environmental specialists, and users with the understanding of environmental issues for munitions and of the ways to improve design and manage potential risks. It covers the various aspects of how chemical properties influence fate, transport, and toxicity of new formulations and prescribes tools for reducing or alleviating environmental risks. In addition, it discusses pyrotechnics and the problem of dealing with munitions underwater. Chapters in Energetic Materials and Munitions: Life Cycle Management, Environmental Impact and Demilitarization look at demilitarization in general, as well as in the future. Topics covered include logistics, costs, and management; life cycle analysis and management; and greener munitions. Another introduces readers to the "One Health" approach in the design of sustainable munition compounds. Following that, readers are taught about land assessment for munitions-related contamination in military live-fire training. The book also examines the development and integration of environmental, safety, and occupational health information.